Using web services to realize service oriented architecture in military communication networks. - Lund, Ketil
The principles of network enabled capability highlight the need for seamless information exchange. The service oriented architectural paradigm has been recognized as one of the key enablers to achieve this. At the same time, Web services have become the de facto standard for implementing service oriented architecture. However, these technologies have been developed for environments with abundant data rates, environments which are very different from military tactical networks. In this article, we present possible solutions and remaining challenges on the way toward also realizing service oriented architecture on the tactical level. Our goal is to make it possible to take advantage of the benefits promised by this architectural paradigm at all military levels, ranging from strategic to tactical networks.
Keywords: Web services; Military communication networks; Military tactical networks; Service oriented architecture